Evaluation of a Virtual Campus Adapted to Web-Based Virtual Reality Spaces: Assessments of Teachers and Students - Rocha Estrada, Francisco Javier; Ruiz-Ramírez, Jessica Alejandra; George-Reyes, Carlos Enrique; Glasserman-Morales, Leonardo David (Frontiers in Education, 2022)
Educational institutions have continuously adapted to new realities in school education, accelerated recently by the COVID-19 pandemic's transformation of learning modalities. This article analyzes teachers' and students' acceptance of a web-based virtual reality (WebVR) tool called Virtual Campus proposed to overcome the limitations of teaching strategies using video conferencing platforms. To measure the acceptance of the Virtual Campus, we designed an instrument based on the Technology Acceptance Model (TAM) that involves variables related to online contexts, the future perception of using the tool, skills development, and appreciation and recommendation. The results indicate that the participants favorably accepted WebVR technology as an alternative teaching methodology in emerging learning scenarios and intend to use it post-pandemic. The best-valued elements were interactions in the socialization spaces, the simulation of presence, and the environmental dynamics. The principal areas of opportunity for improvement were overcoming technical problems and improving the internet connection quality; however, these did not affect the participants' recommendations. Future studies should incorporate variables related to analyzing learning mediated by WebVR-based strategies and using different methodological designs to compare the findings.